O001/#504 Durvalumab, in combination with and following chemoradiotherapy, in locally advanced cervical cancer: results from the phase 3 international, randomized, double-blind, placebo-controlled calla trial. (4th December 2022) - Monk, Bradley; Toita, Takafumi; Wu, Xiaohua; Carlos Limón, Juan; Zhou, Qi; Tarnawski, Rafal; Mandai, Masaki; Shapira-Frommer, Ronnie; Mahantshetty, Umesh; Del Pilar Estevez-Diz, Maria; Ramirez Godinez, Francisco; Varga, Szilvia; et al.
Abstract : Objectives: In locally-advanced cervical cancer (LACC), platinum-based chemoradiotherapy (CRT) has been the standard- of-care treatment for >20 years. CALLA is the first global Phase 3 study evaluating immune checkpoint inhibition (durvalumab) versus placebo in combination with and following CRT in LACC (NCT03830866 ). Methods: Newly-diagnosed, untreated patients with LACC (FIGO 2009 stages IB2-IIB node positive, IIIA-IVA with any node status) were randomized 1:1 to durvalumab (1500 mg IV) or placebo Q4W, for a total of up to 24 months, in combination with and following CRT. CRT comprised concurrent weekly IV cisplatin with EBRT and brachytherapy. RT quality was monitored, with variations evaluated for clinical significance. The primary endpoint is PFS; secondary endpoints include OS, objective response rate, local/distant disease progression incidence, and safety. Results: 770 patients were randomized (N=385 per arm) at 120 sites in 15 countries. Median age was 49 years; median follow-up was 18.5 months. Durvalumab+CRT did not show a statistically significant improvement in PFS vs placebo+CRT (HR 0.84 [95% CI, 0.65–1.08]; P=0.174); there was no detriment to OS, although data were immature and not formally tested. Adverse events of grade 3–4 occurred in 51.7% and 51.0% of patients in the durvalumab+CRT and placebo+CRT arms, respectively; 12.5% and 9.6% of patients discontinued treatment due to AEs possibly related to study drug. Conclusions: Durvalumab in combination with and following CRT did not significantly improve PFS in patients with LACC. Safety of durvalumab+CRT was generally comparable to CRT alone, with no new or unexpected toxicity. Funding: AstraZeneca.